THE CONCEPT AND STRUCTURE OF THE MECHANISM OF PUBLIC ADMINISTRATION - DOROFYEYEV, Oleksandr; PASHNIEV, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The existence of a state without state administration is meaningless and simply impossible without the help of which it broadcasts its will. This is a lever with which regulation can be carried out. The State Administration is designed to activate and actualize the use of all available resources, opening new opportunities, creating stimulating conditions, and maintaining a favorable environment for increasing management efficiency and the population’s quality of life. At the same time, a specific dependence is indicated between the full realization of the accumulated potential and the quality of public administration. It is manifested in the following: the higher the professional management level, the better the existing potential is used and multiplied. Thus, the realization of one’s potential depends on the level of state administration. The regularity of modern management determines this relationship. The state management system forms a management mechanism and with the help of all the main elements of actions of management bodies, target settings, principles, functions, structures, resources, methods, technologies, and management tools. The control mechanism cannot exist without these system components, and at the same time, without the control mechanism, there is no control system. The paper analyzes the interpretation of the term "mechanism of state management" by researchers. It is emphasized that the structure of the mechanism of state administration includes practical measures, means, levers, and incentives, with the help of which state authorities influence society, production, and any social system to achieve the set goals. The main components of the state administration mechanism were studied, and their classification was considered. It emphasizes the distribution of state management mechanisms depending on state management that apply them. The composition of the complex management mechanism is defined, which may include economic, motivational, organizational, political, and legal mechanisms. The author’s vision of defining the term "mechanism of state administration" is given.